If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying j + -15 = 47 Reorder the terms: -15 + j = 47 Solving -15 + j = 47 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + j = 47 + 15 Combine like terms: -15 + 15 = 0 0 + j = 47 + 15 j = 47 + 15 Combine like terms: 47 + 15 = 62 j = 62 Simplifying j = 62
| (6x+5)(8x-9)=0 | | 3log(27)y-1=2 | | 97+b=244 | | 6k+7n=12 | | w+73=502 | | 4x+-10+2x+1=21 | | 4(c+5)=a+b | | 5=x+7-3x | | 8(7x+6)+9(11-x)= | | 149+s=654 | | 4=x+4-4x | | -4(t-4)+9t=3t | | x+3=88 | | 5x-3+6x=-3 | | -9=4(1.5x+6)-2x | | 1+4x-2x^2=0 | | 2412=2n | | 1+4x-2x^3=0 | | 2r=722 | | 11(z+3)-4(z-4)=4(z-3)+2(z-1) | | 9j=342 | | 455=7y | | 9-3(n+6)=-7n-5 | | 6-m-6m=-1 | | 57=33-4(x-2) | | 2*[4x-9]-5=1 | | 15g=450 | | log(x+20)-logx=log(x+20) | | 72=3f | | 4x-(7x-12)= | | 6m=552 | | 8(z+3)-2(z-4)=3(z-3)+2(z-1) |